(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
There is no doubt that the law is entrusted with regulating relations of all kinds between people in all circumstances and conditions, including times of disasters and crises. There is no doubt that contractual obligations are affected by these crises and disasters that may afflict societies such as the Corona pandemic, where the law regulates how to protect the interests of contracting individuals based on the legal principle “the contract is the law of the contracting parties.” The wisdom of this is that the contract is a common desire between two parties whose wills meet on its terms, and therefore it is not fair for one of them to unilaterally modify or cancel it. In violation of this principle, the legislator made the judiciary a way to amend contractual obligations. We will discuss this issue in two sections, the first of which we present to amend contractual obligations according to the theory of emergency conditions, and in the second topic the amendment of contractual obligations according to the concept of force majeure.